Employee Performance Trends in the Digital Age: A Bibliometric Analysis - Loso Judijanto; Tiwuk Herawati; Deti Kurniati; Efi Tajuroh Afiah; Abdul Bahits; Iskandar Pattih (Westscience Press, 2026)
The rapid advancement of digital technologies has fundamentally reshaped how organizations manage work and evaluate employee performance. In response to this transformation, a growing body of scholarly literature has examined the relationship between digitalization and employee performance from multiple disciplinary perspectives. This study aims to map the intellectual structure, thematic evolution, and collaboration patterns of research on employee performance in the digital age using a bibliometric approach. Data were collected from a leading academic database and analyzed using VOSviewer to examine keyword co-occurrence, overlay and density visualizations, as well as co-authorship and country collaboration networks. The results indicate that digital transformation and human resource management constitute the core research themes, closely linked with organizational performance, information management, and knowledge management. Recent trends highlight the increasing prominence of artificial intelligence, leadership, innovation, and sustainability, signaling a shift toward strategic and future-oriented research agendas. Furthermore, collaboration analysis reveals a growing contribution from Asian countries, particularly India and China, alongside fragmented yet evolving international research networks. This study provides a systematic overview of the field and offers insights to guide future research on employee performance in digitally driven organizational contexts⁠.